Furin‐Instructed Intracellular Gold Nanoparticle Aggregation for Tumor Photothermal Therapy - Chen, Jihua; Ma, Yinchu; Du, Wei; Dai, Tianyue; Wang, Yanfang; Jiang, Wei; Wan, Yifei; Wang, Yucai; Liang, Gaolin; Wang, Guangfeng (Advanced functional materials, 2020)
Today, exploring ideal photothermal agents (PTAs) for effective photothermal therapy (PTT) of cancer is an important issue. Cancer‐related enzyme‐instructed aggregation of gold nanoparticles less than 8 nm in diameter will significantly enhance the PTT efficiency of the traditional PTA gold nanoparticle (AuNP). Furin is a type of trans‐Golgi protein convertase upregulated in multiple malignancies. However, furin‐instructed intracellular aggregation of AuNP in cancer cells for PTT of tumor has not yet been reported. Herein, exploiting the advantages of furin and a biocompatible 2‐cyanobenzothiazole‐cysteine (CBT‐Cys) condensation reaction, a furin‐instructed intracellular gold nanoparticle aggregation strategy is developed and a furin‐responsive gold nanoparticle platform (AuNP@1) is designed for effective PTT of cancer both in vitro and in vivo. After being internalized via the high furin‐expression cancer cells, AuNP@1 is subject to a furin‐guided condensation reaction to yield the 1‐Dimers between AuNP@1s, which cross‐link AuNP@1s to form aggregates of AuNP. Experimental results show that formation of AuNP aggregates can largely enhance its photothermal properties, as a result, AuNP@1 shows more efficient photothermal therapeutic effects than its scrambled control AuNP@1‐Scr on MDA‐MB‐468 cells in vitro and MDA‐MB‐468 tumors in vivo. It is envisioned that AuNP@1 can be employed for the clinical PTT of furin‐related cancer in the near future. Upon AuNP@1 internalization by high furin‐expression cancer cells, a CBT‐Cys condensation reaction is initiated to cross‐link AuNP@1s to form gold nanoparticle aggregates. Formation of gold nanoparticle aggregates enhances the photothermal efficiency of gold nanoparticles.